Oral malignant melanoma: a rare case with unusual clinical presentation - Ali, Elneel Ahmed Mohamed (Pan Afr Med J, 2015)
Primary Oral malignant melanoma is a rare tumor with an indigent prognosis. This is a case report of 47-year-old Sudanese female diagnosed as Oral malignant melanoma of the mandible with an unusual pattern of growth and clinical presentation. Furthermore, a possibility of intraosseous origin is suggested.